2016
DOI: 10.1111/scs.12354
|View full text |Cite
|
Sign up to set email alerts
|

Cancer patients' effort to return to normal life: a hermeneutic study

Abstract: Nurses have an obligation to educate patients with cancer about anticipated changes in their life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…An in-depth analysis of the data in the present study showed that the complex and incurable nature of the disease was one of the factors contributing to the aggravation of stigma. Cancer is a complex and multifactorial disease with aggressive and long treatments, and most of the affected people experience great challenges to return to normal life and accept the reality of the disease, treatment, and side effects (33). Treatments often result in hair loss, scars, or other body changes, which may worsen cancerrelated stigma (34).…”
Section: Discussionmentioning
confidence: 99%
“…An in-depth analysis of the data in the present study showed that the complex and incurable nature of the disease was one of the factors contributing to the aggravation of stigma. Cancer is a complex and multifactorial disease with aggressive and long treatments, and most of the affected people experience great challenges to return to normal life and accept the reality of the disease, treatment, and side effects (33). Treatments often result in hair loss, scars, or other body changes, which may worsen cancerrelated stigma (34).…”
Section: Discussionmentioning
confidence: 99%
“…Considered as an incurable disease, its name evokes fear. 14,15 Experience of the spouse of a woman with cancer Neris RR, Zago MMF, Ribeiro MA, Porto JP, Anjos ACY When the patient and her relatives received the news of diagnosis of a disease as "serious" as cancer, their lives became disorganized. Their routines became unsettled, which was reported as a feeling of "shock."…”
Section: Discussionmentioning
confidence: 99%
“…While social support in cancer care is not well-defined, it plays an important role in stabilizing the threat to individual identities [21]. Patients seek emotional and informational support from family, friends, and health care providers throughout their lives with disease [27]. Lack of strong social support and cancer knowledge is one of the most influential factors on stigma [23].…”
Section: Supportmentioning
confidence: 99%
“…Researchers suggest one of the main causes of delay in referring is social stigma of cancer, economic pressures and other organizational barriers[23] [35]. Cultural and educational efforts can increase awareness and reduce the stigma of cancer[27]. Ramacant et al have talked about raising awareness of breast cancer through mass media and television, street camps and colleges, along with group discussions and debates[35].…”
mentioning
confidence: 99%
See 1 more Smart Citation